Late-diagenetic clay mineral assemblages in carbonatized ash beds of the Vaca Muerta Formation (Neuquén Basin, Argentina): Insights into the diagenetic formation of chlorite. (October 2021) - Capelli, Ignacio A.; Scasso, Roberto A.; Cravero, Fernanda; Kietzmann, Diego A.; Vallejo, Dolores; Adatte, Thierry
Abstract: The mineralogical and geochemical composition of carbonatized tephras of the Vaca Muerta Formation (Tithonian-Berriasian) in the Neuquén Basin (Argentina), allows retracing the diagenetic history and the origin of clay minerals in order to establish the sequence of diagenetic transformations and to explain the presence of chlorite in the felsic/intermediate ash beds. The carbonatized ash beds were studied in three sections located in the central part of the Neuquén Basin: El Trapial (ET), Puerta Curaco (PC) and Chacay Melehue (CM). Rock-Eval analyses performed in the enclosing marls revealed that ET section belongs to the oil window, whereas PC and CM to the dry gas window. The clay mineralogy of ET section is mostly constituted by R1/R3 mixed-layer illite/smectite (I/S) type, whereas in PC and CM sections, by highly-crystalline, aluminum-, magnesium-rich chlorite (sudoite) and R1/R3 I/S type. The high-ordered I/S (80–90% illite layers) in the oil window stage indicates that the central part of the Neuquén Basin was characterized by a geothermal gradient higher than previously reported, with an estimated value of 57 °C/km. The absence of any sudoite precursors in ET section and the pervasive distribution of sudoite aggregates in the matrix, suggests that sudoite have precipitated in situ from pore waters. The overmaturation of organic matter in PC and CM sections suggests that precipitation of sudoite occurred during late diagenetic stages, between 150 and 200 °C. The aluminum, magnesium and silicon, essential to sudoite's precipitation were available in the pore waters after the dissolution/recrystallization of minerals and volcanic glass shards present in the tephra. The formation of sudoite was related to the development of the Chos Malal Fold and Thrust Belt, which generated overpressure, deformation and fracturing of the rocks, thus facilitating the circulation of hot waters. Highlights: Ash beds are preserved as early carbonatized concretions in organic-rich mudstones. The clay mineralogy of the ash beds is constituted by I/S and sudoite. Sudoite precipitated in situ, at temperatures between 150 and 200 °C.